Stakeholders` perceptions of athletic career pathways in Paralympic sport: from participation to excellence - Martins Patatas, J.; de Bosscher, V.; Derom, I.; Winckler, C. (Sport in Society: Cultures, Commerce, Media, Politics, 2022)
Athlete development in parasport is a complex domain. Evidence on the developmental trajectories of para-athletes is necessary to examine the critical determinants of specific para-athlete development models. Underpinned by the existing athlete development models to gather insights into the different developmental phases, this study explored how athletic career pathways in parasport are developed by identifying and describing disability-specific characteristics that influence each developmental phase. Para-athlete development was explored through the lens of 32 stakeholders from the Brazilian parasport context who participated in semi-structured interviews. Results ratified the complexity and individuality of para-athlete development, highlighting that the differences according to impairment groups, an early or late start in the sport and the classification, have implications for the development of the phases of athletic pathways in parasport. The findings lend weight toward the need for models other than those traditionally used for able-bodied athletes; rather, para-athlete development models need a disability-specific approach.